USG-guided bilateral sphenopalatine ganglion block: A useful anesthetic adjuvant for trans nasal trans sphenoidal pituitary surgery in a patient with severely low ejection fraction - Ravi Chaudhary; Yashwant S. Payal; Bishnupriya Mohapatra; Sony Sony; Shivam Shekhar (Saudi Journal of Anaesthesia)
Trans-Nasal Trans-Sphenoidal (TNTS) route has become the preferred conduit for operating on a surgically amenable pathology of pituitary gland. The procedure necessitates close monitoring of perioperative hemodynamic stability, especially in patients with impaired heart function. Patients with coronary artery disease (CAD) and compromized cardiac function with very low ejection fraction increase the risk of perioperative major adverse cardiac events (MACE). In this case, a 54-year-old obese female, a known case of CAD post-PTCA with left ventricular systolic dysfunction with apical hypokinesia, complete left bundle branch block with an ejection fraction of 30% with hypertension and diabetes in the last 5 years under medication posted for TNTS excision. A combination of regional and general anesthesia was adopted to curb the sympathetic stimulus, blunt the surgical stress response and pressor response at various stimulating time points, and minimize sympathetic stimulation in the perioperative period. Minimal fluctuation in heart rate and blood pressure during the surgery was observed, which was supposedly attributed to sphenopalatine ganglion (SPG) block and lignocaine. This case underscores the importance of implementation of USG-guided bilateral SPG block and lignocaine infusion and represents a novel approach in perioperative anesthetic management, particularly for cardiac patients undergoing TNTS surgery with low ejection fraction.